Os ingovernáveis - Machado, Silvio Ricardo Munari (2013)
The present study aimed to consider ways of government resistance in contemporary life. The study has started from an archive consisting of twenty field notebooks, which registered an experience of pedagogic coordination in a social project called Pão & Beleza (between 2007 and 2010), realized by Centro de Defesa dos Direitos Humanos de Petrópolis RJ. As reference of life a group of homeless, people served by the project mentioned above, which in this study were called ungovernable, has been taken. To work with this archive the conceptual tools forged by the philosophy of difference and its authors Michel Foucault and Gilles Deleuze has been used seeking to draw a conceptual cartography. This cartography has the affections as a first step towards the conceptual elaboration, ie, first let themselves be influenced by the forces present in the research. These affects force us to think and thereby to create means to make visible and sayable these forces that belongs to the field of sensations. The inconstancy, refusal and courage or truth are the concepts used to outline the common name ungovernable. The inconstancy, which is between the acceptance of a certain mode of government of others over himself and the government of the self over the self; refusal, founding gesture of an ungovernable way of life, and the courage of truth, inspired by cynical, which is an offshoot and a complement of refusal.